2019
DOI: 10.1111/hsc.12791
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health literacy on knowledge, Attitude and decision towards hospice care among community-dwelling seniors

Abstract: The aim of this study was to investigate the relationships between health literacy and hospice knowledge, attitude and decision in community‐dwelling elderly participants. This cross‐sectional study enrolled 990 community‐dwelling elderly participants in three residential areas, with a mean age of 71.53 ± 7.22 years. Health literacy was assessed using the Mandarin version of the European Health Literacy Survey Questionnaire. Knowledge, attitude and decision towards hospice care were assessed using an interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…39 Indeed, evidence has demonstrated that HHL has positive impact on hospice knowledge, attitude and decisionmaking. 40 Our findings corroborated the previous studies' conclusions on the relationship between HL and health care utilization but also expanded an understanding of higher aggressive EOL care among decedents in LHL areas. Education programs to improve HL level could be an effective way to promote hospice use and reduce aggressive care seeking behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…39 Indeed, evidence has demonstrated that HHL has positive impact on hospice knowledge, attitude and decisionmaking. 40 Our findings corroborated the previous studies' conclusions on the relationship between HL and health care utilization but also expanded an understanding of higher aggressive EOL care among decedents in LHL areas. Education programs to improve HL level could be an effective way to promote hospice use and reduce aggressive care seeking behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…This ratio is expected to rise in 2021. "the ability to read, understand, evaluate and use health information to make reasoned and health related decisions" is called health literacy (Huang et al, 2019;p.725). Literacy in health is an important issue, because more literated people will enhance their health-related knowledge and easily access to needed health information.…”
Section: Conceptual Background Ehealth Literacymentioning
confidence: 99%
“…So, eHealth Literacy term is now changing place with health literacy. eHealth Literacy has taken interest of many researchers in the last years and has been the subject of many studies (Tennant et al, 2015;Jacobs et al, 2016;Britt et al, 2017;Panahi et al, 2017;Kayser et al, 2018;Huang et al, 2019;Arcury et al, 2020;Hassan and Masoud, 2020;Lwin et al, 2020;Chang et al, 2021). eHealth Literacy is defined as "the ability to seek out, find, evaluate and appraise, integrate, and apply what is gained in electronic environments toward solving a health problem" by Norman and Skinner (2006;p.2).…”
Section: Conceptual Background Ehealth Literacymentioning
confidence: 99%
“…Studies conducted in different but related contexts support this claim. For instance, Huang et al, (2019) confirmed the positive impact of health literacy on attitude toward staying in hospice care. In another study, Panahi et al, (2017) found a positive correlation between health literacy and attitudes toward the harm of smoking.…”
Section: E-health Literacymentioning
confidence: 71%